Healthcare-Associated Infections in Pediatric Intensive Care Units in Turkey: a National Point-Prevalence Survey - (:unkn) unknown (NATL INST INFECTIOUS DISEASES, 2015)
Health care-associated infections (HCAIs) cause considerable morbidity and mortality in pediatric intensive care units (PICUs). The objective of this point prevalence study was to assess the burden of HCAIs in PICUs in Turkey. Fifty PICUs participated in this study. Data regarding demographics, microbiological findings, therapeutic interventions, and outcomes were collected for all PICU inpatients. A total of 327 patients participated in the study: 122 (37%) experienced 1 or more HCAI. The most frequently reported site of infection was lower respiratory tract (n=77, 63%). The most frequently isolated pathogens were Pseudomonas aeruginosa, Acinetobacter species, and Candida species. Two hundred and forty-seven patients (75%) were receiving antimicrobial therapy at the time of the survey, and the most frequently administered antimicrobials were third generation cephalosporins. Hospital type, male, PICU stay >7 days, and mechanical ventilation were found to be independent risk factors for HCAIs. At the 4-week follow up, 43 (13%) patients had died, 28 (65%) of whom died of HCAIs. Endotracheal intubation, urinary catheter, male, and HCAIs were independent risk factors for mortality. This national, multicenter study documented a high prevalence of HCAIs in Turkey. In light of the 'primum non nocere' principle, the prevention of these infections should be a priority of public health policy.
Keywords: NOSOCOMIAL INFECTIONS; HOSPITAL INFECTION; SURVEILLANCE; MULTICENTER; STATES